188 Improvement of Erectile Dysfunction in Germ Cell Tumor Survivors. (1st May 2022) - Okada, K.; Fujita, K.; Fukuhara, S.; Imanaka, T.; Kuribayashi, S.; Sekii, Y.; Takezawa, K.; Kiuchi, H.; Nonomura, N.
ABSTRACT: Introduction: Germ cell tumors (GCTs) are the most common malignant neoplasms in adolescents and young adults, and most patients with these tumors can be completely cured. Therefore, maintaining quality of life (QOL) is important. Erectile dysfunction (ED) is one factor that reduces the QOL of GCT survivors. Objective: We aimed to clarify the relationship between ED and age, follow-up period, serum levels of hormones, and treatment methods for GCT survivors. Methods: We evaluated ED using the Sexual Health Inventory for Men questionnaire (SHIM) and measured serum levels of hormones in survivors after GCT treatment. The relationships between the SHIM score responses and age, serum levels of hormones, follow-up period, and treatment methods were assessed using a logistic analysis. Results: Fifty-two GCT survivors were enrolled and 46 survivors completed the SHIM. The median age, follow-up period, and SHIM score were 38 years, 35 months, and 18, respectively. Regarding the SHIM scores, 85% had scores <22 and 46% had scores <17. The percentage of SHIM scores <17 was 69% in patients with under 2 years of follow-up. It significantly improved to 33% in patients with over 2 years of follow-up. The multivariate analysis identified the follow-up period as an independent factor for SHIM scores <17. Age, serum levels of hormone, and treatment method were not significant factors for SHIM scores <17. Conclusions: Improvement of SHIM score can be expected after GCT treatment regardless of age, serum levels of hormone, and treatment method. Disclosure: Work supported by industry: no.